Sutura Achillovy slachy vstrebatelným materiálem PDS - Fleiberk, L (Rozhledy v chirurgii, 2001)
The author describes his experience with suture of the Achilles tendon by absorbable material of Ethicon Co. from a small medial incision by minimal traumatization of soft tissues and a somewhat modified postoperative fixation.
Keywords: Male; Female; Achilles Tendon; sutura; Suture Techniques; Absorption; mužské pohlaví; ženské pohlaví; Adult; Achillova šlacha; Sutures; ruptura; polydioxanon; šicí techniky; Rupture; dospělí; Polydioxanone; absorpce; lidé; Humans